DETERMINANTS OF INDONESIA NON-OIL AND GAS EXPORTS TO NON-TRADITIONAL MARKET - Siti Aisyah; Trias Dewi Renggani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Indonesia has considerable opportunities to export non-oil/gas to various countries. Non-traditional market is considered to have great potential for increasing non- oil exports. This study aims to estimate the effect of GDP of export destination countries, inflation of export destination countries, economic openness of export countries and the Indonesian exchange rate against the US dollar to Indonesia non-oil exports to non-traditional trading partner countries. The analytical method in this study uses descriptive statistical analysis and panel data regression, the results show that REM is the selected model. The GDP has a significant and positive affect to Indonesia’s exports, while exchange rate has no effect on Indonesia’a exports, inflation having a significant and negative effect to Indonesia’a exports, and economic openness having an significant and positive effect to Indonesia’a exports. Indonesia needs to diversify exports to non-traditional countries and cannot rely solely on exports to major trading partner countries. Keywords: exports, non-traditional markets, GDP, inflation, exchange rates, economic openness